PELAKSANAAN LAYANAN E-PUSKESMAS DI PUSKESMAS AMBACANG KECAMATAN KURANJI KOTA PADANG - Arya Bagus Saputro; M. Fachri Adnan; Zikri Alhadi (JPSI (Journal of Public Sector Innovations), 2018)
The purpose of this research is to know the implementation of e-Puskesmas service at Ambacang Community Health Center of Kuranji Subdistrict, Padang City, to know the supporting and inhibiting factors in the implementation of e-Puskesmas service at Ambacang Community Health Center. This research is a qualitative research with descriptive method. This research was conducted at Puskesmas Ambacang Kecamatan Kuranji Kota Padang. The research by purposive sampling. The data collected are secondary data and primary data through interview, observation and documentation study. Test data validity is done with trianggulasi then data analyzed by reducing data, display data the results of this study indicate that the implementation of e-Puskesmas service has not been implemented properly so that the implementation of the service becomes not effective. Supporting factors were found to be sufficient budget in applying e-Puskesmas, a change of paradigm of staff at Ambacang Community Health Center. Inhibiting factors are lack of adequate infrastructure availability, internet connectivity level is not appropriate, lack of socialization about e-Puskesmas service.